2008
DOI: 10.1159/000134918
|View full text |Cite
|
Sign up to set email alerts
|

Transcutaneous Electrogastrography in Patients with Ileus

Abstract: Background: The aim of the prospective study was to characterize the disturbance of gastric electrical control activity in different types of ileus and to correlate surface electrogastrography (EGG) findings with a set of inflammatory markers. Patients and Methods: Fifty-four adult patients with mechanic, vascular and paralytic ileus proven on clinical and radiological exams and 14 age- and sex-matched controls were examined. Gastric myoelectrical activity was recorded using 3 Ag-AgCl disposable skin electrode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Several experimental studies have reported the important role of IL-6 in the development of POI. Even little manipulation of the bowel induces activity of IL-6, which results in activation of nitric oxide and prostaglandins and causes migration of leucocytes into the circular muscle of the bowel and ends up with PPOI eventually [ 21 24 ]. However, with fruitful data obtained from animal studies, clinical attempts to predict POI by determining inflammatory mediator levels, the important mechanism in PPOI pathophysiology, remain limited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several experimental studies have reported the important role of IL-6 in the development of POI. Even little manipulation of the bowel induces activity of IL-6, which results in activation of nitric oxide and prostaglandins and causes migration of leucocytes into the circular muscle of the bowel and ends up with PPOI eventually [ 21 24 ]. However, with fruitful data obtained from animal studies, clinical attempts to predict POI by determining inflammatory mediator levels, the important mechanism in PPOI pathophysiology, remain limited.…”
Section: Discussionmentioning
confidence: 99%
“…Zhu et al found that peritoneal levels of IL-1, IL-6, and procalcitonin were higher in PPOI patients [ 10 ], indicating localized parameters are sensitive for PPOI prediction. Clinical data also found that IL-6 levels are higher in patients undergoing open surgery when compared with patients undergoing laparoscopic surgery [ 21 ], while open procedures had been demonstrated to delay recovery of POI [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is clear evidence that specific inflammatory transcription factors, cytokine and chemokine upregulation, and leukocyte recruitment have a very significant part to play, with a direct inhibitory effect on the muscularis externa of the bowel [83, 115,[134][135][136]. Furthermore, this affect seems to be age-dependent, with an increase in the proinflammatory mediator expression with increasing age [136].…”
Section: Ileusmentioning
confidence: 99%
“…In an animal experiment, abdominal laparotomy induced elevated serum IL-6 levels and inhibition of gastrointestinal transit in the same time course ( 12 ). In a human study, elevated serum IL-6 levels after abdominal surgery were involved in delayed recovery of gastric emptying and impaired gastric electrical activity in patients with postoperative ileus ( 13 , 14 ). Although these data have indicated the possible role of IL-6 in the development of POI, there is still a lack of clinical studies focusing on the association between postoperative alterations in IL-6 and the recovery of colonic motility of transit among patients undergoing surgical resection for colorectal cancer.…”
Section: Introductionmentioning
confidence: 99%